2017
DOI: 10.1177/0263617416687563
|View full text |Cite
|
Sign up to set email alerts
|

Development of cobalt-doped alumina hybrids for adsorption of textile effluents

Abstract: The discharge volume and composition of textile effluents gain scientific concern due to hazardous and biotoxic nature of azo dyes. Azo dyes are non-biodegradable due to its complex molecular structure and recalcitrant nature. Serious attempts have been made to synthesize and develop new materials to combat the environmental problems. The present study is designed for removal of azo dyes (Methyl orange, Congo red and Basic fuchsine) from synthetic aqueous solutions and real textile effluents. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, it is estimated that for the processing of about 12-20 tons of raw material are discarded daily between 1000 and 3000 m 3 of wastewater, thus promoting significant impacts on the environment (Ghaly, 2014). In addition, wastewater from activities in this sector has around 20% of dyes (Hynes et al, 2020;Khattab et al, 2020;Berradi et al, 2019), which are potentially toxic (Hynes et al, 2020;Benkhaya et al, 2020;Berradi et al, 2019;Verma et al, 2019;Obaid et al, 2016) generating negative impacts on the environment in terms of salinity, biological oxygen demand (BOD), chemical oxygen demand (COD), pH, temperature and others (Hynes et al, 2020;Berradi et al, 2019;Parveen & Rafique, 2018;Roy et al, 2018;Sarkar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is estimated that for the processing of about 12-20 tons of raw material are discarded daily between 1000 and 3000 m 3 of wastewater, thus promoting significant impacts on the environment (Ghaly, 2014). In addition, wastewater from activities in this sector has around 20% of dyes (Hynes et al, 2020;Khattab et al, 2020;Berradi et al, 2019), which are potentially toxic (Hynes et al, 2020;Benkhaya et al, 2020;Berradi et al, 2019;Verma et al, 2019;Obaid et al, 2016) generating negative impacts on the environment in terms of salinity, biological oxygen demand (BOD), chemical oxygen demand (COD), pH, temperature and others (Hynes et al, 2020;Berradi et al, 2019;Parveen & Rafique, 2018;Roy et al, 2018;Sarkar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their main finding was combustible waste produced from agriculture and industry sectors and further reused as an auxiliary fuel. Parveen and Rafique (185) developed an optimal technique without the use of additional chemicals at the time of pre-and post-treatment, and also studied the cost-benefit analysis of the proposed efficient method. They showed that the cost analysis of the aluminum salt and foil separately and reported that as the aluminum foil was a waste material it can be recycled and reused with a low operational cost.…”
Section: Study On the Cost-benefit Analysis Of Textile Wastewater Usementioning
confidence: 99%